2011
DOI: 10.1097/rlu.0b013e3181f9e038
|View full text |Cite
|
Sign up to set email alerts
|

Palpation Thyroiditis Seen on F-18 FDG PET/CT

Abstract: A 29-year-old woman presented with a new right supraclavicular mass on a background of resection of a malignant melanoma from her right shoulder before 4 years. F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) imaging revealed uptake in a right supraclavicular node and the inferior pole of the left lobe of the thyroid gland. Subsequent resection and histology of the right supraclavicular node and the left lobe of the thyroid gland demonstrated metastatic melanoma and palpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They named this pathologic entity ''palpation thyroiditis,'' concluding that it was due to palpation of the thyroid gland at surgery. It was generally thought to be of little clinical importance, except for rare case reports of patients who developed thyrotoxicosis following manipulation of the thyroid gland during surgery (633)(634)(635)(636). However, a recent study suggested that the rate of transient overt or subclinical thyrotoxicosis following parathyroid surgery may be as high as 30%, although there was likely ascertainment bias because not all patients had postoperative TSH levels measured (637).…”
Section: And Recommendation 118mentioning
confidence: 99%
“…They named this pathologic entity ''palpation thyroiditis,'' concluding that it was due to palpation of the thyroid gland at surgery. It was generally thought to be of little clinical importance, except for rare case reports of patients who developed thyrotoxicosis following manipulation of the thyroid gland during surgery (633)(634)(635)(636). However, a recent study suggested that the rate of transient overt or subclinical thyrotoxicosis following parathyroid surgery may be as high as 30%, although there was likely ascertainment bias because not all patients had postoperative TSH levels measured (637).…”
Section: And Recommendation 118mentioning
confidence: 99%